The Influence of Globalization on the Decisions of the Marketing Complex - Alimienė, Monika; Kuvykaitė, Rita (Ekonomika, 2002)
Many Lithuanian companies are currently seeking new foreign markets. Success of international business depends on a company’s experience abroad, its resources, skills and effective marketing. In the global market are especially important the decisions of the marketing complex. The article evaluates of the changing conditions of business activities in foreign markets, analyses globalization’s influence on a company’s marketing decisions, and discusses the strategies of marketing complex elements in the global market. The results of research on decision making in the global marketing of Lithuanian mineral, chemical, plastic, rubber industry companies operating in foreign markets are presented and the marketing complex decisions in these companies are evaluated.